UNIT 9.22 Whole Genome Sequencing: A Considered Approach to Clinical Implementation. (April 2013) - Dimmock, David
Abstract: The recent entry of "whole" exome/"whole" genome sequencing into limited clinical practice has led to a progression of the availability of genome‐scale testing beyond deletion/duplication copy number arrays. This unit provides a considered approach to the implementation of such testing in routine clinical practice. Specifically, we will highlight the challenges in patient selection and consent, and the technical issues surrounding test interpretation and reporting. The unit will then provide practical solutions that allow for genome‐wide sequencing to be implemented in current clinical practice. Curr. Protoc. Hum. Genet. 77:9.22.1‐9.22.7. © 2013 by John Wiley & Sons, Inc.